Selective Aerobic Oxidation of a Metal–Organic Framework Boosts Thermodynamic and Kinetic Propylene/Propane Selectivity - Wang, Yu; Huang, Ning‐Yu; Zhang, Xue‐Wen; He, Hai; Huang, Rui‐Kang; Ye, Zi‐Ming; Li, Yang; Zhou, Dong‐Dong; Liao, Pei‐Qin; Chen, Xiao‐Ming; Zhang, Jie‐Peng (Angewandte Chemie International Edition, 2019)
Efficient adsorptive separation of propylene/propane (C3H6/C3H8) is highly desired and challenging. Known strategies focus on either the thermodynamic or the kinetic mechanism. Here, we report an interesting reactivity of a metal–organic framework that improves thermodynamic and kinetic adsorption selectivity simultaneously. When the metal–organic framework is heated under oxygen flow, half of the soft methylene bridges of the organic ligands are selectively oxidized to form the more polar and rigid carbonyl bridges. Mixture breakthrough experiments showed drastic increase of C3H6/C3H8 selectivity from 1.5 to 15. For comparison, the C3H6/C3H8 selectivities of the best‐performing metal–organic frameworks Co‐MOF‐74 and KAUST‐7 were experimentally determined to be 6.5 and 12, respectively. Gas adsorption isotherms/kinetics, single‐crystal X‐ray diffraction, and computational simulations revealed that the oxidation gives additional guest recognition sites, which improve thermodynamic selectivity, and reduces the framework flexibility, which generate kinetic selectivity. Tailoring with O2: When a flexible metal–organic framework is heated in a flow of oxygen, half of the organic ligands are selectively oxidized, thereby adding guest recognition sites and reducing the flexibility of the pores. As a result, the thermodynamic and kinetic selectivity for propylene/propane separation improve simultaneously.